2008
DOI: 10.1021/jf801101u
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Immunostimulatory Polysaccharide from an Herb Tea, Gynostemma pentaphyllum Makino

Abstract: Water-soluble polysaccharide from Gynostemma pentaphyllum herb tea (PSGP) was isolated by hot-water extraction and ethanol precipitation. The chemical components and preliminary immunomodulating activity of PSGP were investigated both in vitro and in vivo. Capillary zone electrophoresis analysis showed that PSGP was a typical nonstarch heteropolysaccharide, with glucose being the main component monosaccharide (23.2%), followed by galactose (18.9%), arabinose (10.5%), rhamnose (7.7%), galacturonic acid (4.7%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 30 publications
2
54
0
Order By: Relevance
“…The sulfate radical content in CCPS was tested by barium chloride-gelatin assay, with potassium sulfate as the standard (Lloyd & Dodgson, 1961). The moisture content was measured by drying CCPS at 110 C for 2 h and calculating the amount of evaporated water (Yang et al, 2008). The ash content was determined by incinerating CCPS overnight in a neytech vulcan furnace at 550 C and weighing the residue (Yang et al, 2008).…”
Section: General Characterization Of Ccpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sulfate radical content in CCPS was tested by barium chloride-gelatin assay, with potassium sulfate as the standard (Lloyd & Dodgson, 1961). The moisture content was measured by drying CCPS at 110 C for 2 h and calculating the amount of evaporated water (Yang et al, 2008). The ash content was determined by incinerating CCPS overnight in a neytech vulcan furnace at 550 C and weighing the residue (Yang et al, 2008).…”
Section: General Characterization Of Ccpsmentioning
confidence: 99%
“…The moisture content was measured by drying CCPS at 110 C for 2 h and calculating the amount of evaporated water (Yang et al, 2008). The ash content was determined by incinerating CCPS overnight in a neytech vulcan furnace at 550 C and weighing the residue (Yang et al, 2008).…”
Section: General Characterization Of Ccpsmentioning
confidence: 99%
“…Another study demonstrating the hepatoprotective effect of polysaccharides from Huangshan Maofeng green tea also found that the main monosaccharide components of this polysaccharide were galactose (mol.%, 35.0%), arabinose (28.9%) and galacturonic acid (11.3%) (55). Capillary zone electrophoresis analysis showed that polysaccharide isolated from Gynostemma pentaphyllum Makino consisted of glucose (23.2%), galactose (18.9%), arabinose (10.5%), rhamnose (7.7%), galacturonic acid (4.7%), xylose (3.9%), mannose (3.1%), and glucuronic acid (1.2%) (56). Characterization of polysaccharides from two Pleurotus mushrooms, P. eryngii and P. ostreatus, found that they were mainly composed of mannose, along with other monosaccharides, including glucose, galactose, xylose and rhamnose (57,58).…”
Section: Sources Of Polysaccharides Targeting Growth Factors In Hccmentioning
confidence: 99%
“…A broad series of components including polysaccharose and glycine betaine from L. barbarum fruit have been identified as an important class of bioactive natural products, possessing many important properties of pharmacological relevance. Many functional components in L. barbarum, including flavonoids, carotenoids and polysaccharides, have been reported to be closely associated with the health-enhancing effect (Sheng et al, 2007;Yang, Zhao, Yang, & Ruan, 2008).…”
Section: Introductionmentioning
confidence: 99%